2014
DOI: 10.2337/db13-0606
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Zinc Transporter-8 Gene (SLC30A8) and Plasma Zinc Concentrations for Impaired Glucose Regulation and Type 2 Diabetes

Abstract: Although both SLC30A8 rs13266634 single nucleotide polymorphism and plasma zinc concentrations have been associated with impaired glucose regulation (IGR) and type 2 diabetes ( T2D), their interactions for IGR and T2D remain unclear. Therefore, to assess zinc-SLC30A8 interactions, we performed a case-control study in 1,796 participants: 218 newly diagnosed IGR patients, 785 newly diagnosed T2D patients, and 793 individuals with normal glucose tolerance. After adjustment for age, sex, BMI, family history of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 41 publications
5
60
1
Order By: Relevance
“…insulin AUC and proinsulin:insulin at 5 and 10 min), suggesting that our findings are in fact true for our study population. Also, a recent cross-sectional study in Chinese participants demonstrated that the inverse association between plasma zinc and diabetes was attenuated in those with the RR genotype [35]; these results are consistent with our finding that zinc may be most beneficial in those with the W allele. Our WW genotype group was too small to make conclusions regarding its response.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…insulin AUC and proinsulin:insulin at 5 and 10 min), suggesting that our findings are in fact true for our study population. Also, a recent cross-sectional study in Chinese participants demonstrated that the inverse association between plasma zinc and diabetes was attenuated in those with the RR genotype [35]; these results are consistent with our finding that zinc may be most beneficial in those with the W allele. Our WW genotype group was too small to make conclusions regarding its response.…”
Section: Discussionsupporting
confidence: 92%
“…While our findings for the RR genotype group were unexpected, consistency in the direction of effect of changes in acute insulin release and proinsulin:insulin as well as recent studies of rs13266634 [25, 35] lend support to our overall findings. Moreover, the complexity of SLC30A8 variation is highlighted by a recent study demonstrating that some rare loss-of-function mutations in SLC30A8 actually decrease diabetes risk [48] and that nutrient interactions with rs13266634 may be sensitive to baseline nutrition status [39].…”
Section: Discussionsupporting
confidence: 86%
“…This single nucleotide polymorphism (SNP) rs1326663 causes the replacement of an arginine residue with a tryptophan (R325W) in the cytosolic Cterminus of the transporter. Possession of the risk variant of rs13266634 is associated with a 17% increase in disease risk per allele [65]. R325 allele carriers also present an increased proinsulin:insulin ratio during an oral glucose tolerance test [66], an impaired insulin secretion during an intravenous glucose tolerance test [67] and lower β cell function (HOMA-B assessment) [68].…”
Section: Znt8 and T2d: Gwas Studiesmentioning
confidence: 99%
“…The cases were consecutively recruited from patients diagnosed as having new-onset type 2 diabetes at the outpatient clinics of the Department of Endocrinology at the Tongji Medical College Hospital during the period of January 2012-December 2014. Concomitantly, we recruited healthy individuals who were frequency matched by age (65 y) and sex to cases from an unselected population undergoing a routine health checkup in the same hospital, as described elsewhere (20,21). We excluded participants who had any of the following conditions: age ,30 y, BMI (in kg/m 2 ) $40, a history of diagnosed diabetes, a history of pharmacologic treatment of hyperlipidemia, any clinically systemic disease, any acute illness, or chronic inflammatory or any infective disease.…”
Section: Study Populationmentioning
confidence: 99%